Together on Retreat Meeting Jesus in Prayer - James Martin (HarperOne, 2013)
How can we find God? How can we pray? What can we learn about Jesus from the New Testament stories about his ministry around the Sea of Galilee? In this innovative e-book, Rev. James Martin, S.J. invites us on an actual retreat to answer those questions and to encounter God's presence in prayer and meditation. Martin, an experienced spiritual guide, teaches you how to pray with Scriptures and answers your questions about prayer in ways that are accessible to both doubtful seekers and devout believers. This fresh, insightful and personal retreat experience is a must for anyone looking to explore this ancient practice in a contemporary way. Includes reflection questions for personal study or reading groups, as part of the full retreat experience.